1984
DOI: 10.5361/jkmu1956.36.supplement_s43
|View full text |Cite
|
Sign up to set email alerts
|

"Fosterage Experiments" and Other Supplementary Experiments Related to Ferric Nitrilotriacetate (Fe-NTA) -induced "F1 Amyloidosis"

Abstract: Our previous study showed that chronic exposure of the offspring of ICR/JCL mice to ferric nitrilotriacetate (Fe-NTA) , both the parents of which had been exposed to the same antigen, induced generalized amyloidosis in 69% of them. The amyloidotic offspring of 13 families obtained were designated as Fe-NTA-induced "F1 amyloidosis" mice. 16)The above study allows us a brief speculation that multiple injections of Fe-NTA stimulated chronically, and proliferated selectively F1 mouse clones to respond better to Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…25 ml of a Freundtype emulsion containing additional heat-killed M. butyricum (40 mg/m1), regarding 10 different mouse strains investigated, obvious strain-dependent differences in theS -159 incidence and degree of severity of amyloidosis were noted. 20)On the basis of results of their "fosterage experiments", Ogura et al18) also suggested that the immunological memory for the antigen (Fe-NTA conjugate) remaining in the F1 mouse blood, transmitted before birth via the placenta, may have caused F1 mice, regularly given Fe-NTA, to respond much more strongly to the antigen than their maternal mice, resulting in macrophage dysfunction and subsequent amyloid synthesis. That is, in the experiments where the Fe-NTA injections were suspended for about 7 weeks in the period from crossing to weaning, minimum ofF1 mouse serum iron, transmitted via the placenta, is supposed to have contributed to the development of "F1 amyloidosis".…”
mentioning
confidence: 99%
“…25 ml of a Freundtype emulsion containing additional heat-killed M. butyricum (40 mg/m1), regarding 10 different mouse strains investigated, obvious strain-dependent differences in theS -159 incidence and degree of severity of amyloidosis were noted. 20)On the basis of results of their "fosterage experiments", Ogura et al18) also suggested that the immunological memory for the antigen (Fe-NTA conjugate) remaining in the F1 mouse blood, transmitted before birth via the placenta, may have caused F1 mice, regularly given Fe-NTA, to respond much more strongly to the antigen than their maternal mice, resulting in macrophage dysfunction and subsequent amyloid synthesis. That is, in the experiments where the Fe-NTA injections were suspended for about 7 weeks in the period from crossing to weaning, minimum ofF1 mouse serum iron, transmitted via the placenta, is supposed to have contributed to the development of "F1 amyloidosis".…”
mentioning
confidence: 99%